2020
DOI: 10.1007/s11694-020-00661-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and cytotoxic activities of sulfated polysaccharides from five different edible seaweeds

Abstract: In recent times, there has been a growing interest in the exploration of antioxidants and global trend toward the usage of seaweeds in the food industries. The low molecular weight up to 14 kDa sulfated polysaccharides of seaweeds (Portieria hornemannii, Spyridia hypnoides, Asparagopsis taxiformis, Centroceras clavulatum and Padina pavonica) were evaluated for in vitro antioxidant activities and cytotoxic assay using HeLa cell line and also characterized by FTIR. The high yield (7.74% alga dry wt.) of sulfated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…Therefore, this red seaweed extract also demonstrated to be efficient in the inhibition of fungal growth, namely, Aspergillus fumigatus , Aspergillus terreus, and Aspergillus flavus [ 220 ]. Moreover, these seaweed sulfated polysaccharides were found to be antioxidant and non-cytotoxic to HeLa cells [ 221 ]. Furthermore, a study revealed that A. taxiformis aqueous extract, even in low concentration (1.5%), reveals an antiviral effect on crop plants production due to its phytohormones content, such as cytokinins and auxins [ 222 ].…”
Section: Pharmacological Potential Of the Invasive Seaweedsmentioning
confidence: 99%
“…Therefore, this red seaweed extract also demonstrated to be efficient in the inhibition of fungal growth, namely, Aspergillus fumigatus , Aspergillus terreus, and Aspergillus flavus [ 220 ]. Moreover, these seaweed sulfated polysaccharides were found to be antioxidant and non-cytotoxic to HeLa cells [ 221 ]. Furthermore, a study revealed that A. taxiformis aqueous extract, even in low concentration (1.5%), reveals an antiviral effect on crop plants production due to its phytohormones content, such as cytokinins and auxins [ 222 ].…”
Section: Pharmacological Potential Of the Invasive Seaweedsmentioning
confidence: 99%
“…For example, a study assessing several red algae species and found that the brown algae P. pavonica showed higher antioxidant activity than several red algae (Table 4). This study suggest that the content of sulfate is not the main parameter that affects antioxidant response, but the type of monomers also play an important role (Arunkumar et al 2021). Besides, different investigations have concluded high levels of uronic acid, protein and low M W can lead to stronger DPPH and ABTS scavenging activity (Chen et al 2020).…”
Section: Antioxidantmentioning
confidence: 74%
“…Also, fucoidan from P. pavonica reduced SPC-A-1 tumor weight up to 50% at 40 mg/kg and increased apoptosis rates up to 40% with 300 mg/mL. In addition, this fucoidan extract showed inhibition against the proliferation of HeLa cells (IC 50 = 1.059 µg/mL) (Arunkumar et al 2021), whereas SP obtained from A. rigida had significant anticancer activity against breast cancer BCCL cells (IC 50 = 40 µg/mL) (Gopu and Selvam 2020). In a recent study exploring the use of fucoidan nanoparticles, it was reported that found their IC 50 (20 µg/mL) against PANC-1 cells was 2.3 folds lower than fucoidan extracts (IC 50 = 53 µg/mL) (Table 4).…”
Section: Antitumormentioning
confidence: 89%
“…Among such preservative molecules, carbohydrates have deserved special attention. Remarkably, the antioxidant activity of polysaccharide compounds obtained from aqueous extracts of red algae has been detected in in vitro studies focused on Porphyra yezoensis [14], Gracilaria corticata [17], and Spyridia hypnoides, Asparagopsis taxiformis, Portieria hornemannii, and Centroceras clavulatum [41]. According to these studies, the current inhibition of lipid oxidation development could be explained on the basis of the remarkable presence of carbohydrate compounds that were shown to be present in the starting alga flour, according to the proximate composition analysis.…”
Section: Antioxidant Activity Of Red Alga Extractsmentioning
confidence: 99%